miR-155 is involved in Alzheimer’s disease by regulating T lymphocyte function - Song, Juhyun; Lee, Jong Eun (Frontiers in Aging Neuroscience, 2015)
Alzheimer's disease (AD) is considered the most common cause of sporadic dementia. In AD, adaptive and innate immune responses play a crucial role in clearance of amyloid beta and maintenance of cognitive functions. In addition to other changes in the immune system, AD alters the T-cell responses that affect activation of glial cells, neuronal cells, macrophages, and secretion of pro-inflammatory cytokines. These changes in the immune system influence AD pathogenesis. Micro-RNA (miRNA)-155 is a multifunctional miRNA with a distinct expression profile. It is involved in diverse physiological and pathological mechanisms, such as immunity and inflammation. Recent studies indicate that miR-155 regulates T-cell functions during inflammation. In this article, we summarize recent studies describing the therapeutic potential of miR-155 via regulation of T cells in AD. Further, we propose that regulation of miR-155 might be a new protective approach against AD pathogenesis.